Case Files Biochemistry / Eugene C. Toy, William E. Seifert, Henry W. Strobel - Toy, Eugene C.
Experience with clinical cases is key to excelling on the USMLE Step 1 and shelf exams, and ultimately to providing patients with competent clinical care. Case Files: Biochemistry provides 53 true-to-life cases that illustrate essential concepts in this field. Each case includes an easy-tounderstand discussion correlated to essential basic science concepts, definitions of key terms, biochemistry pearls, and USMLE-style review questions. With Case Files, you’lllearn instead of memorize.